2020
DOI: 10.1002/humu.24090
|View full text |Cite
|
Sign up to set email alerts
|

Familial Mediterranean fever: Penetrance of the p.[Met694Val];[Glu148Gln] and p.[Met694Val];[=] genotypes

Abstract: The penetrance of the p.[Met694Val];[Met694Val] genotype of pyrin in adult familial Mediterranean fever (FMF) patients is close to 100%. Disease penetrance of the p.[Met694Val];[Glu148Gln] genotype (M694V/E148Q), and the heterozygous p.[Met694Val];[=] genotype is unknown. A difference in the penetrance of the latter two may indicate functionality for the p.Glu148Gln variant. We performed a penetrance estimation study using controls and patients of North African Jewish (NAJ) decent. FMF in this population is hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…34,35 The penetrance of compound heterozygosity of M694V/E148Q was found to be higher than heterozygous M694V, thus implicated in the pathogenesis. 36 However, similar to our results, a recent study showed that compound heterozygosity of M694V with E148Q did not result in a clinically different disease than M694V heterozygotes and suggested as a benign variation. 37 Several inflammatory conditions were shown to be associated with FMF and more frequently detected in the presence of M694V mutation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…34,35 The penetrance of compound heterozygosity of M694V/E148Q was found to be higher than heterozygous M694V, thus implicated in the pathogenesis. 36 However, similar to our results, a recent study showed that compound heterozygosity of M694V with E148Q did not result in a clinically different disease than M694V heterozygotes and suggested as a benign variation. 37 Several inflammatory conditions were shown to be associated with FMF and more frequently detected in the presence of M694V mutation.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, E148Q was associated with a milder form of FMF in children from Turkey 34,35 . The penetrance of compound heterozygosity of M694V/E148Q was found to be higher than heterozygous M694V, thus implicated in the pathogenesis 36 . However, similar to our results, a recent study showed that compound heterozygosity of M694V with E148Q did not result in a clinically different disease than M694V heterozygotes and suggested as a benign variation 37 …”
Section: Discussionsupporting
confidence: 86%
“…In our study, most patients with NOD2/MEFV variants were heterozygous for MEFV E148Q. Several studies of its pathogenic role in classic FMF were conducted with mixed results ( 35 ), but most literature data have favored its contributory role in autoinflammatory phenotypes that may or may not be classified as typical FMF as is the case with two recent independent Turkish studies ( 36 , 56 ). An Israeli study showed that MEFV E148Q is likely a contributory genetic factor when coinherited with M694V ( 35 ).…”
Section: Discussionmentioning
confidence: 49%
“…Observational studies have shown that p.E148Q could potentially increase the effect of moderate alleles such as p.V726A and p.R761H [ 8 , 9 ] . A recent penetrance study in 148 patients referred for FMF found a penetrance 17 times higher for the genotype [(E148Q)];[(M694V)] (p.E148Q and p.M694V in trans ) than [=];[(M694V)] (p.M694V heterozygous) (0.135 and 0.008, respectively) [ 10 ]. Also two recent, independent studies support that p.E148Q could influence the severity of FMF in individuals with a heterozygous B30.2 domain mutation and increase the level of IL-18 cytokine expression at remission in those individuals [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%